Benefits of Externships with Pediatric Dentistry Programs for Potential Residents: Program Directors' and Current Residents' Perceptions. Issue 3 (1st March 2014) - Klein, Ulrich; Storey, Bryan; Hanson, Peter D.
Abstract : This study's goal was to understand the extent, framework, and benefits of externships with prospective residency programs undertaken by predoctoral dental students or dentists interested in applying for a residency program. In 2012, a questionnaire was sent to all pediatric dentistry residents and program directors in the United States (63 percent and 74 percent return rate, respectively). Externships were offered by fifty–seven of the seventy–six programs. Most program directors (95 percent) agreed that externships are beneficial and compensate at least partially for the lack of numerical National Board Dental Examination scores or class rankings. Among the responding residents, 61 percent were female. The top reasons given by residents for choosing to extern with a certain program were its location and perceived reputation. Of the 249 respondents who did an externship, 47 percent externed with their current program. The acceptance rate into the number one choice of program was similar among those who did an externship vs. those who did not (73 percent vs. 75 percent). No relationship was found between gender and externships among the 341 respondents who were accepted into their top choice. Most of the residents (98.8 percent) felt that completing an externship was beneficial, and 88 percent got an increased understanding for the differences between university– and non–university–based residency programs.